A Photographic Reconstruction of Aldo van Eyck’s Own House: Fragment and Collage - Campos Uribe, Alejandro; Lacomba Montes, Paula (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2017)
This paper analyses the existing photographs of Aldo van Eyck’s first house in Amsterdam. Firstly, the carefully staged photographs by J.Versnel are used to build a biography of architectural concepts. With their help, the house is described as a test field where the architect explores for the first time different architectural: polycentrism, relativity, psychogeography. The house, built at the same time as the first playground in Bertelmanplein (1947), inaugurates a new way of designing: from the collage of autonomous fragments to a net of points of interest held by reciprocal relations. Secondly, the already published photographs by Versnel are completed by a stack of unpublished sketches and negatives. Using all of them, the history of the house and the conversions made by its inhabitants are traced. Although the photographs have been used to unravel the architectural reasons of the house, they could also show the way of living of Aldo van Eyck and his family. If the first pictures by Versnel clarify the adjectives architectural criticism uses to describe Van Eyck’s projects, the new negatives found in his archive can be used to understand the definition of architecture coined by Van Eyck in his articles: “architecture is built homecoming”. The photographs, all together, define architecture as an unfinished process that makes itself in its daily use.
Keywords: Aldo van Eyck; Photography; Binnenkant; Polycentrism; Photographic reconstruction